Morfofisiologia comparada de Lotus spp. de diferentes hábitos de crescimento - Maroso, Rita Poles (2006)
This work had the objective to compare cultivars of Lotus corniculatus (São Gabriel, ARS2620) and L. uliginosus (Maku) through time analysis of morphological development as well as understanding the subterraneous system. The plants were cultivated in pots and they were harvested at 90, 120, 150, 180 e 210 days after seeding. The cultivars had the same temporal trend in relation to height, root volume and shoot dry matter (DM) differing for the magnitude of the changes. The DM accumulation was superior in the cvs. Maku (15 g.plant-1) and S. Gabriel (14 g.plant-1) in relation to cv. ARS2620 (11 g.plant-1). The cultivars differed (P<0,05) for plant and crown diameter, root system length and crown stem number. The subterraneous system is a diffuse type formed by roots and soboles, being the last one more vigorous for the cv. Maku, not having rhizomes in any cultivars